The Correlation Between Students’ Critical Thinking And Their Speaking Skill - Ulviani Ulviani; Ari Prasetyaningrum; Muhammad Adib Nazri; Laila Wati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aimed at finding out the correlation between students’ critical thinking and their speaking skill. This research used quantitative method and a correlational research design. The sample of this research was 20 students who were taken from XI class of students of PPS ULYA RUMAH QURAN NW LOMBOK in the academic year of 2023 - 2024. The sample was taken by Purposive Sampling Technique. The instruments of this research were questionnaire and public speaking test. The result of this research showed there is negative correlation between their critical thinking and speaking skill. Based on the data analyzed by using SPSS, the researcher found that the coefficient correlation was 0.128. Therefore the significance of students’ critical thinking and their speaking skill is at the rate of 0.590, which means the significant value smaller than 0.05 (0.590 > 0.05).